2014
DOI: 10.1242/dev.106633
|View full text |Cite
|
Sign up to set email alerts
|

A microdevice to locally electroporate embryos with high efficiency and reduced cell damage

Abstract: The ability to follow and modify cell behaviour with accurate spatiotemporal resolution is a prerequisite to study morphogenesis in developing organisms. Electroporation, the delivery of exogenous molecules into targeted cell populations through electric permeation of the plasma membrane, has been used with this aim in different model systems. However, current localised electroporation strategies suffer from insufficient reproducibility and mediocre survival when applied to small and delicate organisms such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 72 publications
0
13
0
Order By: Relevance
“…At the same time, DVE cells maintain their epithelial characteristics, and exchange neighbors along the migration pathway [35,37]. This behavior not only characterizes the leading DVE cells, but also surrounding cells that will contribute to the AVE [38], establishing this as a coordinated, or collective, cell migration. Genetic studies have identified roles for actin regulators Rac1 and the WAVE complex as well as PTEN in this migration [35,39,40], consistent with the active, directed protrusive behavior.…”
Section: Migration and Intercalation In The Avementioning
confidence: 96%
“…At the same time, DVE cells maintain their epithelial characteristics, and exchange neighbors along the migration pathway [35,37]. This behavior not only characterizes the leading DVE cells, but also surrounding cells that will contribute to the AVE [38], establishing this as a coordinated, or collective, cell migration. Genetic studies have identified roles for actin regulators Rac1 and the WAVE complex as well as PTEN in this migration [35,39,40], consistent with the active, directed protrusive behavior.…”
Section: Migration and Intercalation In The Avementioning
confidence: 96%
“…Temporary in vitro cultivation of embryos at these stages is known to be feasible [72,73]. Therefore, many researchers performed gene delivery (via in vitro EP or injection of viral vectors) into dissected postimplantation embryos to assess gene function, cell movement, and cell lineage [74][75][76][77][78][79][80]. For example, Mellitzer et al [76] microinjected a solution containing dsRNA (100 ng/µL) directed against orthodenticle homeobox 2 (Otx2) or forkhead box protein A2 (Foxa2) and fast green dye into the amniotic cavity of an isolated embryo (Day 7.5 of pregnancy), as shown in Figure 4A.…”
Section: Gene Delivery To Postimplantation Embryos At Somite Stagementioning
confidence: 99%
“…These data are similar to the one associated with the best conditions used to run our original SU-8 / Parafilm chip (4). However, thanks to the simulations the present optimal parameters were obtained after a very limited number of tests, ~ 12 per device, whereas in our initial screening work on the first design we performed more than 200 electroporations (4). Finally, it is worth noting that permeation localization also stayed satisfactory since the shape of the dielectric guides was roughly kept constant during the technological evolution process.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, microsystem performances could be demonstrated by addressing at E5.5 the distal visceral endoderm (DVE), a migrating cell population essential for anterior-posterior axis establishment. Live imaging of cells discretely labeled with fluorescent proteins allowed us to reveal new facts concerning tissue rearrangement (4). Besides, we showed that the utilization of our device could be extended to a variety of embryological contexts, from preimplantation embryos to organ explants dissected from latter stage organisms (4).…”
Section: Introductionmentioning
confidence: 90%